Порівняльний аналіз архітектури обробки сповіщень на стороні back-end: синхронного REST API та асинхронного підходу з Apache Kafka - Старіченко, В. С.; Лановий, О. Ф. (ХНУРЕ, 2025)
This work is devoted to a comparative analysis of synchronous REST API and asynchronous Apache Kafka approaches for notification processing archІТecture on the back-end side. The study examines key aspects such as performance, scalabilІТy, error-handling mechanisms, and fault tolerance. The results demonstrate that Kafka provides better fault tolerance and scalabilІТy under high loads, while REST API offers simpler implementation and immediate feedback. The research provides practical recommendations for choosing the optimal archІТectural approach depending on system requirements.
Keywords: архітектура обробки; сповіщення back-end